Effects of single and 7-fold administration of a complex of albendazole with disodium salt of glycyrrhizic acid to hamsters infected with Opisthorchis felineus - D. F. Avgustinovich; M. N. Lvova; M. A. Tsyganov; D. V. Ponomarev; V. A. Mordvinov; V. I. Evseenko; A. V. Dushkin (Российский паразитологический журнал, 2021)
The purpose of the research is to evaluate the effect of albendazole as part of the supramolecular complex with disodium salt of glycyrrhizic acid obtained by solid-phase mechanical treatment.Materials and methods. The anthelmintic activity of the complex and its effect on the host organism was assessed on hamsters infected with Opisthorchis felineus by single and 7-fold administration at 45 days after infection. After 21 days, we counted the number of helminthes in the liver, and conducted a morphometric analysis of the liver and spleen, and detected biochemically the activity of alanine aminotransferase and aspartate aminotransferase in the animals’ blood serum.Results and discussion. The number of O. felineus significantly decreased after 7-fold, but not a single, administration of albendazole (ABZ) and ABZ-Na2GA complex (1 : 10). The administrated substances had no effect on the weight gain of the animals and the daily consumption of the pellets. At the same time, ABZ only as part of the complex normalized the weight of the liver and spleen in hamsters infected with O. felineus and reduced the alanine aminotransferase activity. Consequently, a longer administration of ABZ as part of the complex with disodium glycyrrhizinate has not only a pronounced anthelmintic effect, but also improves some of the physiological parameters of hamsters to a greater extent than a pure substance.